The role of free nucleotides in heart failure - E. V. Kolesnikova; O. V. Myachina; A. N. Pashkov; A. A. Pashkova (Кардиоваскулярная терапия и профилактика)
Aim. To assess the potential of studying the plasma level of free nucleotides as additional biomarkers of heart failure (HF) taking into account the clinical and paraclinical data of the patient, and to analyze its change during therapy.Material and methods. The study included 67 patients with HF and 23 healthy volunteers. The plasma content of free nucleotides was analyzed by chromatography on an automated FPLS® System (Sweden), 10 × 200 mm column with Q Sepharose Fast Flow. Repeated analysis was performed in patients with a reduced ejection fraction after 6±0,2 months.Results. In patients with HF, compared with the control group, we found lower levels of adenosine — 30,45±2,61 vs 56,68±3,99 mm2 (p=0,001), adenosine monophosphate — 278,60±18,60 vs 391,68±39,86 mm2 (p=0,022), guanosine diphosphate — 500,27±22,83 vs 901,63±51,09 mm2 (p=0,001), adenosine triphosphate — 49,25±8,89 vs 145,18±18,80 mm2 (p=0,001), guanosine triphosphate — 32±8,25 vs 92,40±27,07 mm2 (p=0,041) and higher adenosine diphosphate values — 690,10±57,41 vs 392,09±32,63 mm2 (p=0,002). These patterns were preserved when analyzing taking into account the ejection fraction, functional class and the presence of diabetes. During treatment, the levels of adenosine diphosphate and guanosine diphosphate significantly change (up to 307±26,08 mm2 and 650,47±58,1 mm2, respectively), approaching the values in the control group.Conclusion. The revealed features of the nucleotide profile in HF make it possible to consider the level of free nucleotides as an additional potential biomarker reflecting objective disorders at the cellular level.